Penerapan DES Method Untuk Memprediksi Jumlah Harga Pasar Tanaman Holtikultura Kota Tanjungbalai - Indah Sapitri (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Price is one of the variables that must be controlled properly, because the price will greatly affect several aspects of the company's activities. Price is also something that is given up in exchange for goods or services. Prices can change quickly. Market price is one of the variables that are properly controlled and obtained from an item or service offered in the market. Market prices meet at the point where supply and demand meet. The market price of vegetables is currently a serious problem for farmers, especially in the Tanjungbalai City area, because market prices continue to experience unstable changes so that it is very difficult for farmers to predict the future. Fluctuating market prices can also result in large profit losses and have an impact on farmers' losses. To be more efficient, the author designed a forecasting system using PHP programming and MySQL database. The final result of this research is that the algorithm with the Double Exponential Smoothing calculation can be applied to the process of forecasting the market price of hoticulture plants, making it easier to determine the market price of hoticulture plants in the next period.